A Mathematics Learning Outcome Test Characterized by Higher-Order Thinking Skills for Grade V Elementary School Students - Ariyana, I Komang Sesara; Sariyasa, Sariyasa (ZERO: Jurnal Sains, Matematika dan Terapan, 2024)
This research was aimed at developing the results of learning mathematics characteristics of higher-order thinking skills (HOTS) in the form of multiple choice for grade V elementary school students. This research applied D & D model by Richey & Kleine (2007). HOTS in this study were able to transfer, critical thinking, and solve problems. These aspects are included in Analyzing, Evaluating, and Developing category. Math questions which HOTS were Multi step problems and non-routine questions. The sample of the test experiment was 112 students drawn from four elementary schools in Singaraja Town. The results showed that of 21 items that had been made, there were 20 valid items. The difficulty analysis showed five unfit grains, 14 items were categorized as difficult and one item was categorized as moderate. By the discrimination index, there were two items categorized as high, nine items were categorized as moderate, and four items were categorized as low. The effectiveness of the distractors was fulfilled in all questions. These fifteen items have a degree of reliability of 0.609.